2022
DOI: 10.3390/ijerph19159756
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Machine Learning Scheme for Predicting Mammographic Anomalies in High-Risk Individuals Using Questionnaire-Based Predictors

Abstract: This study aimed to investigate the important predictors related to predicting positive mammographic findings based on questionnaire-based demographic and obstetric/gynecological parameters using the proposed integrated machine learning (ML) scheme. The scheme combines the benefits of two well-known ML algorithms, namely, least absolute shrinkage and selection operator (Lasso) logistic regression and extreme gradient boosting (XGB), to provide adequate prediction for mammographic anomalies in high-risk individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…We proposed an integrated multi-step ML scheme (Figure 1) to construct a decisiontree model for risk evaluation in patients with NVAF taking different doses of dabigatran. Our protocol applied four ML algorithms: naive Bayes (NB), CART, random forest (RF), and extreme gradient boosting (XGBoost), which have been widely used in various medical informatics applications to select important variables [36][37][38][39][40].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We proposed an integrated multi-step ML scheme (Figure 1) to construct a decisiontree model for risk evaluation in patients with NVAF taking different doses of dabigatran. Our protocol applied four ML algorithms: naive Bayes (NB), CART, random forest (RF), and extreme gradient boosting (XGBoost), which have been widely used in various medical informatics applications to select important variables [36][37][38][39][40].…”
Section: Methodsmentioning
confidence: 99%
“…LGR is a classic classification method that uses data fitting to a logistic function to estimate the likelihood of an event occurring [40]. The multivariate LGR model, which uses numerical or categorical predictor variables, was commonly used in medical research and as the benchmark method for comparing the performance of these ML methods.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study [14] concluded that age was the most impactful factor in predicting positive mammography findings. To further scrutinize the effects of other risk factors on mammography outcomes, this study stratified participants into two groups: women aged 45-49 and 50-54.…”
Section: Introductionmentioning
confidence: 95%
“…XGB or SGB can effectively identify important variables when the variables have nonlinear and/or high dimensional interactions. [8] SGB was implemented in R by the Generalized Boosted Regression Models (GMB) Package. [9] The hyperparameters of the SGB classifier are n.trees, shrinkage, and n.minobsinnode.…”
Section: Stochastic Gradient Boostingmentioning
confidence: 99%